Female Genital Tract Congenital Malformations : Classification, Diagnosis and Management - Grimbizis, Grigoris F.; Campo, Rudi.; Gordts, Stephan; Tarlatzis, Basil C (London : Springer London : Imprint: Springer, 2015)
Using the new ESHRE/ESGE classification system, this book presents all uterine, cervical and vaginal anomalies in a systematic way. The diagnostic work-up of women with female genital malformations is reviewed in an evidence-based fashion, taking into account the availability of new non-invasive diagnostic methods. The treatment strategies and the therapeutic alternatives to restore health are also critically reviewed.   Female Genital Tract Congenital Malformations: Classification, Diagnosis and Management assesses all the latest information concerning the pathogenesis, diagnosis and treatment of female genital malformations. It is a vital manual for all trainees and practitioners within the fields of obstetrics and gynecology, radiologists, researchers in the field of human reproduction, fertility specialists, endoscopists, and ultrasonographers
Part 1: basics -- 1. Normal embryological development of the female genital tract -- 2. Pathogenesis and aetiology of female genital malformations -- 3. Implantation in women with uterine congenital malformations -- 4. Classification of female genital malformations.-Part 2: Screening and diagnosis of female genital malformations -- 5. Hysterosalpingography -- 6. 2D Ultrasound and sonohysterography for the diagnosis of Female Genital Anomalies -- 7. 3D Ultrasound -- 8. Magnetic resonance imaging for the Diagnosis of Female Genital Anomalies -- 9. Diagnosis of Uterine Congenital Anomalies: Endoscopy -- 10. Current Work-Up for Screening And Diagnosing Female Genital Malformations -- Part 3: Clinical implications of the female genital malformations -- 11. Prevalence in the general and selected populations -- 12. Health problems related to female genital malformations: obstructive and complex anomalies -- 13. Fertility in women with uterine anomalies -- 14. Pregnancy outcome in women with uterine anomalies -- 15. Cervical Weakness in women who have uterine anomalies: Impact on pregnancy outcomes.- Part 4: Treatment of vaginal aplasia / techniques and results -- 16. Frank dilators -- 17. Vulvo-Perineoplasty Creatsas Vaginoplasty -- 18. Neovagina formation with expansion of vaginal vault -- 19. Neovagina formation with the use of peritoneum -- 20. Neovagina formation with the use of bowel -- 21. Vaginal Aplasia: Critical Overview of Available Treatment Options -- Part 5: Treatment of obstructive anomalies -- 22. Vaginal septae and imperforate hymen -- 23. Treatment of Obstructing Anomalies: Cervical aplasia -- 24. Treatment of Patients with Non-communicating Horns with Cavity -- Part 6: Treatment of uterine malformations -- 25. T-shaped uterus -- 26. Septum resection: Techniques and Post-Treatment Reproductive Performance -- 27. Bicorporeal uterus: treatment options -- 28. Bicorporeal Uterus: Laparoscopic Metroplasty -- Part 7: Disorders of sex development -- 29. Disorders of Sex Development: Classification and Treatment
1 13
Keywords: Diagnosis, Ultrasonic; Endoscopic surgery; Gynecology; Interventional radiology; Medicine; Reproductive Medicine; Surgery